RELATIONSHIP AND IMPACT OF SLEEP PATTERNS ON MENTAL, PHYSICAL HEALTH, RISK OF CHRONIC DISEASES - Mayshila Mahmud; Atha Thazkira Nasution; Suhaila Nabila; Hafiza Isra; Darin Keysa Imtiyaz (PT. Radja Intercontinental Publishing, 2025)
Healthy sleep patterns are an important component in maintaining physical, mental, and emotional health. Poor sleep patterns, such as insufficient sleep duration or irregular sleep, have been shown to have significant impacts on various aspects of health, including mental health, blood pressure, risk of chronic disease, and physical balance. This study used a literature study method to analyze various studies covering populations of adolescents, young adults, college students, and the elderly. The results of the analysis showed that poor sleep patterns in adolescents are associated with an increased risk of anxiety and depression. In college students, irregular sleep patterns affect gastrointestinal health and academic performance. Local research shows that lack of sleep contributes to increased blood pressure, while poor sleep patterns in the elderly population increase the risk of falls and fractures. In addition, research using wearable devices revealed that irregular sleep patterns increase the risk of obesity, hypertension, and mental health disorders.